The Hopf algebra structure of the Z3-graded quantum supergroup GLq,j(1|1) - Celik, Salih; Yasar, Erguen (AMER INST PHYSICS, 2008)
In this work, we give some features of the Z(3)-graded quantum supergroup. (C) 2008 American Institute of Physics.
Keywords: DEFORMATION; GL(1/1); Physics